Acute and chronic fluid misdirection syndrome: pathophysiology and treatment - Grzybowski, Andrzej (Graefes Arch Clin Exp Ophthalmol, 2017)
PURPOSE: To summarize our current understanding of the specific pathogenic mechanisms of the fluid misdirection syndrome and possible treatment methods. METHODS: We used the PubMed web platform to find relevant studies using the following keywords: infusion misdirection syndrome, aqueous misdirection syndrome, ciliary block, ciliovitreal block, capsular block, intraoperative fluid misdirection, subcapsular fluid entrapment, acute intraoperative rock-hard eye syndrome, positive vitreous pressure glaucoma, and malignant glaucoma. Other publications were also considered as a potential source of information when referenced in relevant articles. RESULTS: We collected and analyzed 55 articles dated from 1951 to 2016. Acute intraoperative rock-hard eye syndrome is characterized by a very shallow anterior chamber with the absence of suprachoroidal effusion or hemorrhage and no noticeable pathology of the iris–lens diaphragm. It usually occurs during uneventful phacoemulsification, particularly in hyperopic eyes. The pathophysiology of acute fluid misdirection syndrome is based on inappropriate movement of balanced salt solution via the zonular fibers. This syndrome has also been described as occurring from hours to months, or years, after the initial surgery. The pathophysiology of malignant glaucoma is based on similar mechanisms of cilio-lenticular block of aqueous flow leading to the misdirection of aqueous posteriorly into or besides the vitreous gel. Faced with these situations, vitreous decompression is required, preferably with hyaloido-capsulo-iridectomy. In phakic eyes, concomitant cataract extraction would be desirable. CONCLUSIONS: We believe both of these clinical conditions should be considered as one syndrome. We suggest the term acute fluid misdirection syndrome for the cascade of events during phacoemulsification surgery. Chronic fluid misdirection syndrome better describes the nature of malignant glaucoma.